In Silico Designing and Screening of Antagonists against Cancer Drug Target XIAP - Kumar, Rahul; Chauhan, Jagat Singh; Raghava, Gajendra Pal Singh (Current cancer drug targets, 2015)
X-linked inhibitor of apoptosis (XIAP) is a member of inhibitor of apoptosis (IAP) family and involved in the suppression of apoptosis in cancer cells. This property makes it a therapeutic target for the cancer therapy. In the present study, we have developed QSAR models using chemical descriptors, fingerprints, principal components, docking energy parameters and similarity-based approach against XIAP. We have achieved correlation (R) of 0.803 with R(2) value of 0.645 at 10-fold cross validation using SMOreg algorithm. We have evaluated these models on independent dataset to ascertain its robustness and achieved correlation (R) of 0.793 with R(2) value of 0.628. Further, we have used these models for the screening of FDA approved drugs and drug-like molecules from ZINC database and prioritized them on the basis of their predicted pIC50 values. Docking studies of top hits with XIAP-BIR3 domain shows that Iodixanol (DB01249) and ZINC68678304 have higher binding affinities than well-known tetrapeptide inhibitor, AVPI. We have integrated these models in a web server named as "XIAPin". We hope that this web server will contribute in the designing of nifty antagonists against XIAP.